Exploring the Political Potential of the Local State: Building a Dialogue with Sheffield in the 1980s. Issue 3 (8th January 2023) - Beveridge, Ross; Cochrane, Allan
Abstract: This article explores the political potential of the local state through an engagement with the case of Sheffield City Council in the 1980s. The new municipalism movement has generated renewed interest in the "local" and "urban" as transformative projects. The local state holds a pivotal if problematic role in these debates, often seen as the decisive force facilitating or impeding transformation. In building a dialogue with 1980s Sheffield, we provide a less certain account of the local state's potential. Sheffield occupies an ambiguous position within and beyond traditional municipal labourism and therefore provides a potent example to explore tensions within municipalism between state and autonomist visions of politics. In Sheffield, radical intent turned into a more cautious governmental programme in the city, notwithstanding glimpses of political alternatives. The experience of those years provides insights on the contingencies of bringing movements and state politics together in what was then called "local socialism". Zusammenfassung: Dieser Beitrag untersucht das politische Potenzial des lokalen Staates am Beispiel des Sheffield City Council (UK) in den 1980er Jahren. Die politische Bewegung des neuen Munizipalismus führte zu einem neuen Interesse am „Lokalen" und „Urbanen" als transformative Projekte. Der lokale Staat spielt in diesen Debatten eine zentrale, wenn auch komplizierte Rolle, da er oft als die entscheidende Kraft angesehen wird, die den Wandel sowohl erleichtert als auch behindert. Mit dem Beispiel von Sheffield der 1980er Jahre liefern wir eine weniger eindeutige Darstellung des Potenzials des lokalen Staates. Sheffield nimmt eine ambivalente Position innerhalb und jenseits des traditionellen „Municipal Labourismus" ein und bietet daher ein überzeugendes Beispiel für die Untersuchung der Spannungen innerhalb des Munizipalismus zwischen staatlichen und autonomen Visionen von Politik. In Sheffield verwandelte sich ein ursprüngliches radikales Programm in ein vorsichtigeres Regierungsprogramm, auch wenn es durchaus Anzeichen für politische Alternativen gab. Die Erfahrungen der 1980er‐Jahre geben Aufschluss über die Kontingenz der Zusammenarbeit von sozialen Bewegungen und staatlicher Politik in dem, was damals „lokaler Sozialismus" genannt wurde.